2008
DOI: 10.1111/j.1600-065x.2008.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐associated proteins as potential therapeutic targets

Abstract: Integrins are adhesion receptors important for hematopoiesis, leukocyte trafficking, and formation of immunological synapses; hence, they may provide targets for therapeutic intervention in leukocyte-driven pathologies. Blocking integrin-ligand binding is one strategy for inhibiting integrins; however, a complete loss of integrin function can lead to mechanism-based toxicities. Because integrin alpha and beta subunits interact with a variety of other proteins to receive and transmit cellular signals, targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 176 publications
(276 reference statements)
2
55
0
Order By: Relevance
“…Antagonists of α4 have shown promise in the treatment of autoimmune disorders such as multiple sclerosis and Crohn's disease, but the associated toxicities have led to the design of alternative approaches other than those directed at blocking integrin-ligand binding (40,41). Blocking α4 signaling may have important implications with respect to ablation of tumor vasculature, as it has been recently demonstrated that homing of progenitor cells to tumor areas undergoing active angiogenesis uses the α4 integrin/VCAM1 counter receptor pair (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Antagonists of α4 have shown promise in the treatment of autoimmune disorders such as multiple sclerosis and Crohn's disease, but the associated toxicities have led to the design of alternative approaches other than those directed at blocking integrin-ligand binding (40,41). Blocking α4 signaling may have important implications with respect to ablation of tumor vasculature, as it has been recently demonstrated that homing of progenitor cells to tumor areas undergoing active angiogenesis uses the α4 integrin/VCAM1 counter receptor pair (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…However, actin also plays an important role in the 2B4-independent adhesion of NK cells to tumor target cells. The b 1 and b 2 integrins are linked to the actin cytoskeleton through talin, which has been shown to be essential for inside-out signaling (31). Additionally, LFA-1 in NK cells has the unique ability to transmit its own inside-out signal to other LFA-1 molecules (32).…”
Section: Discussionmentioning
confidence: 99%
“…As a cell adhesion molecule, integrin participates in these cellular processes by mediating the adhesion of cells to the ECM and by transmitting signals that regulate these processes. Integrins are promising targets for the treatment of inflammatory and autoimmune diseases (3).…”
Section: Introductionmentioning
confidence: 99%